2010
DOI: 10.1007/s00228-010-0835-0
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 activity comparison between Swedes and Koreans: effect of genotype, sex, oral contraceptive use, and smoking

Abstract: Objectives To compare CYP2C19 enzyme activity between Swedes and Koreans controlling for the effect of CYP2C19 genotype, sex, oral contraceptive use and smoking habit.Methods CYP2C19 activity was determined in 185 healthy Swedish and 150 Korean subjects as omeprazole/5-hydroxyomeprazole ratio (metabolic ratio; MR) using high-performance liquid chromatography. Genotyping was performed by PCR using Taqman assay.Results As expected, a higher incidence of poor metabolizers (PM) was found in Koreans (14%) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 29 publications
(33 reference statements)
2
35
0
1
Order By: Relevance
“…In the study by Ramsjö et al [38], it was reported that the cut-off in Koreans was as high as -3.04, while it was a low -0.86 17 in a Swedish cohort. The cut-off value separating the PM and IM phenotypes in this study was -1.152, which is within the range of cut-off values previously reported.…”
Section: Phenotypingmentioning
confidence: 94%
See 1 more Smart Citation
“…In the study by Ramsjö et al [38], it was reported that the cut-off in Koreans was as high as -3.04, while it was a low -0.86 17 in a Swedish cohort. The cut-off value separating the PM and IM phenotypes in this study was -1.152, which is within the range of cut-off values previously reported.…”
Section: Phenotypingmentioning
confidence: 94%
“…Previous studies have reported CYP2C19 phenotypic cut-off values, separating PMs from IMs/EMs, to range between log MR (5OH/OME) -0.6 and -3.04 [32,38,39]. In the study by Ramsjö et al [38], it was reported that the cut-off in Koreans was as high as -3.04, while it was a low -0.86 17 in a Swedish cohort.…”
Section: Phenotypingmentioning
confidence: 96%
“…Further support for this observation comes from C EDITORIAL a novel in vitro pharmacodynamic assay, which demonstrated that CYP3A4/5 isoenzymes play a significant role in both hepatic oxidation steps of clopidogrel. 11 Among subjects homozygous for CYP2C19*1, Koreans displayed significantly lower CYP2C19 enzyme activity than Swedes (P<0.000001), 12 which may imply that CYP3A4/5 enzyme activity plays a more important role in clopidogrel metabolism among Koreans. The addition of cilostazol in PCI-treated patients has been shown to reduce major cardiovascular events such as mortality, myocardial infarction and stent thrombosis.…”
Section: Article P 2581mentioning
confidence: 99%
“…For example, Korean subjects carrying the CYP2C19*1/*1 gene had higher a metabolic ratio than Swedish subjects (1.48 vs. 0.58; P < 0.000001), indicating lower CYP2C19 activity in Koreans [6]. However, the contribution of the CYP2C19 LoF allele to platelet reactivity appears similar during clopidogrel treatment.…”
mentioning
confidence: 94%
“…East Asians with the same genotype as Caucasians have shown lower CYP2C19 activity [3,6]. For example, Korean subjects carrying the CYP2C19*1/*1 gene had higher a metabolic ratio than Swedish subjects (1.48 vs. 0.58; P < 0.000001), indicating lower CYP2C19 activity in Koreans [6].…”
mentioning
confidence: 99%